Tawâfuq Bunûd al-As’ilah li Mâdat al-Lughah al-‘Arabiyyah fi al-Imti?an al-Nihâ’I al-Wa?anî - Iis Makhisoh (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2021)
Purpose-assessments conducted at the national level require good quality in these assessment instruments. This research focuses on analyzing item of the arabic final exam questions with the standard indicators set by the ministry of religion for the 2021 madrasahs’ final exams (UM). Design/Methodology/Approach- the researcher used the quantitative approach and the quantitative non-experimental method. As for the basic data are the question items for the Arabic language and the standards set by the Ministry of Religion 2021. the next data is the student's answer items needed to measure reliability and validity. Analysis of the suitability of the questions using a percentage scale, added with Bloom's taxonomy; to measure reliability the anates program was used. Findings— the results are (1) the arabic language questions tested in jombang are in accordance with the UM standars with a validiity score 92%, (2) as bloom's taxonomy, the cognitive level shows that 42.5% are at level one, 3% at cognitive level two, and 27.5% at cognitive level three. (3) the anates program got reliability score of 0.83. Research Limitation - collecting much data is difficult because some schools use a randomization program, made the required data cannot be included in the anates.